2020
DOI: 10.1097/pai.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of Epithelial-Mesenchymal Transition and Tumor Proliferation Markers in GLi-1-positive Oral Squamous Cell Carcinoma

Abstract: In oral squamous cell carcinoma (OSCC), involvement and activation of the Hedgehog pathway (HH) may be related to epithelial-mesenchymal transition and cell proliferation. The present study aimed to evaluate epithelial-mesenchymal transition and proliferative potential in OSCC cases demonstrating activation of the HH pathway. Twenty-three GLi-1-positive OSCC cases were submitted to immunohistochemical detection of Snail, Slug, N-cadherin, E-cadherin, β-catenin, and MCM3 proteins. Clinicalpathologic immunoexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that the HH pathway plays a crucial role in tumor growth and invasion in HNSCC. Therefore, increased expression of SHH, PTCH1, SMO, GLI1, GLI2, and GLI3 was detected significantly more frequently in advanced HNSCC tumors [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In most cases, progressing HNSCC invades the mandible or maxilla, what leads to bone destruction.…”
Section: Aberration Of Hh Signaling Pathway In Hnsccmentioning
confidence: 99%
“…Several studies have demonstrated that the HH pathway plays a crucial role in tumor growth and invasion in HNSCC. Therefore, increased expression of SHH, PTCH1, SMO, GLI1, GLI2, and GLI3 was detected significantly more frequently in advanced HNSCC tumors [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In most cases, progressing HNSCC invades the mandible or maxilla, what leads to bone destruction.…”
Section: Aberration Of Hh Signaling Pathway In Hnsccmentioning
confidence: 99%
“…The main cause of the poor therapeutic effect of OSCC treatments is that the molecular mechanisms underlying the progression of OSCC remains unknown. Interestingly, some studies (Cho et al, 2019;Hao et al, 2019) have indicated that the Snail/Slug signaling pathway is involved in the development of OSCC (Dantas et al, 2021;Jiang et al, 2016). However, the detailed mechanisms by which Snail/Slug regulates OSCC is still elusive.…”
Section: Introductionmentioning
confidence: 99%